ZAP isoforms regulate unfolded protein response and epithelial- mesenchymal transition - Ly, Phuong Thao (2023)
Human ZAP inhibits many viruses, including HIV and coronaviruses, by binding to viral RNAs to promote their degradation and/or translation suppression. However, the regulatory role of ZAP in host mRNAs is largely unknown. Two major alternatively spliced ZAP isoforms, the constitutively expressed ZAPL and the infection-inducible ZAPS, play overlapping yet different antiviral and other roles that need further characterization. We found that the splicing factors hnRNPA1/A2, PTBP1/2, and U1-snRNP inhibit ZAPS production and demonstrated the feasibility to modulate the ZAPL/S balance by splice-switching antisense oligonucleotides in human cells. Transcriptomic analysis of ZAP-isoform-specific knockout cells revealed uncharacterized host mRNAs targeted by ZAPL/S with broad cellular functions such as unfolded protein response (UPR), epithelial-mesenchymal transition (EMT), and innate immunity. We established that endogenous ZAPL and ZAPS localize to membrane compartments and cytosol, respectively, and that the differential localization correlates with their target-RNA specificity. We showed that the ZAP isoforms regulated different UPR branches under resting and stress conditions and affected cell viability during ER stress. We also provided evidence for a different function of the ZAP isoforms in EMT-related cell migration, with effects that are cell-type dependent. Overall, this study demonstrates that the competition between splicing and IPA is a potential target for the modulation of the ZAPL/S balance, and reports new cellular transcripts and processes regulated by the ZAP isoforms.